KUALIFIKASI DAN IMPLIKASI MENGHALANGI PROSES PERADILAN TINDAK PIDANA KORUPSI [Qualifications and Implications of the Obstruction of Justice in Corruption Judicial Process] - Ade Mahmud (Law Review, 2021)
The rule of law of the criminal obstruction of the judicial process raises the debate because it has the flexibility and is applied selectively by law enforcers resulting in injustice. This study aims to determine the qualifications of criminal acts of corruption that hinder the judicial process and analyze the implications of the modus operandi of corruption that hinders the judicial process. This research method using the normative law approach because studying norm, principles relating to Obstruction of Justice offense. The qualification of the offense of Obstruction of Justice may be limited by the method of grammatical interpretation, which implies the word (a) “prevent” is interpreted as restraining, prohibiting the meaning of acts aimed at corruption criminal proceedings unfulfilled; (b) “blocking” interpreted to obstruct, interfere, disturbing, meaning the act aimed to prevent the judicial process from being obstructed and whether the objective is achieved or not is a requirement; and (c) “thwarted” is interpreted as unsuccessful/failed means that the judicial process against corrupt perpetrators is unsuccessful and the business succeeds. The modus operandi of the Obstruction of Justice offense through the power of the community, legal counsel, and political channels implies (a) inhibition of law enforcement efforts; (b) difficulties in the development of cases; and (c) causes high-cost law enforcement.Bahasa Indonesia Abstrak: Aturan hukum tindak pidana menghalangi proses peradilan (Obstruction of Justice) menimbulkan perdebatan karena memiliki kelenturan dan diterapkan secara tebang pilih oleh penegak hukum, sehingga menimbulkan ketidakadilan. Penelitian ini bertujuan untuk menentukan kualifikasi tindak pidana korupsi yang menghalangi proses peradilan dan menganalisis implikasi modus operandi tindak pidana korupsi yang menghalangi proses peradilan. Metode penelitian ini menggunakan pendekatan hukum normatif karena mengkaji kaidah, asas-asas yang berkaitan dengan delik Obstruction of Justice. Kualifikasi delik Obstruction of Justice dapat dibatasi dengan metode penafsiran gramatikal yang memaknai kata (a) “mencegah” dimaknai sebagai menahan, melarang artinya perbuatan yang bertujuan agar proses peradilan tindak pidana korupsi tidak terlaksana; (b) “merintangi” dimaknai menghalang-halangi, mengganggu, mengusik, artinya perbuatan yang ditujukan agar proses peradilan terhalang dan apakah tujuan tersebut tercapai atau tidak bukan merupakan syarat; dan (c) “menggagalkan” dimaknai tidak berhasil/menjadi gagal, artinya proses peradilan terhadap pelaku tindak pidana korupsi tidak berhasil dan usaha tersebut berhasil. Modus operandi delik Obstruction of Justice melalui kekuatan masyarakat, kuasa hukum dan jalur politik yang berimplikasi pada (a) terhambatnya upaya penegakan hukum; (b) kesulitan dalam pengembangan kasus; dan (c) mengakibatkan penegakan hukum berbiaya tinggi.